Editor's Choice-The role of the emergency department in the management of acute heart failure: An international perspective on education and research - Pang, Peter S.; Collins, Sean P.; Miro, Oscar; Bueno, Hector; Diercks, Deborah B.; Di Somma, Salvatore; Gray, Alasdair; Harjola, Veli-Pekka; Hollander, Judd E.; Lambrinou, Ekaterini; Levy, Phillip D.; Papa, AnnMarie; et al. (My University, 2017)
Emergency departments are a major entry point for the initial management of acute heart failure (AHF) patients throughout the world. The initial diagnosis, management and disposition - the decision to admit or discharge - of AHF patients in the emergency department has significant downstream implications. Misdiagnosis, under or overtreatment, or inappropriate admission may place patients at increased risk for adverse events, and add costs to the healthcare system. Despite the critical importance of initial management, data are sparse regarding the impact of early AHF treatment delivered in the emergency department compared to inpatient or chronic heart failure management. Unfortunately, outcomes remain poor, with nearly a third of patients dying or re-hospitalised within 3 months post-discharge. In the absence of robust research evidence, consensus is an important source of guidance for AHF care. Thus, we convened an international group of practising emergency physicians, cardiologists and advanced practice nurses with the following goals to improve outcomes for AHF patients who present to the emergency department or other acute care setting through: (a) a better understanding of the pathophysiology, presentation and management of the initial phase of AHF care; (b) improving initial management by addressing knowledge gaps between best practices and current practice through education and research; and (c) to establish a framework for future emergency department-based international education and research.
Keywords: Emergency department; Acute heart failure; Patient management; Education; Outcome